The effect of heat stress on some productive indicators of broilers in coastal conditions - حسن, فداء; بشرى العيسى,; ماجد موسى, (Latakia University Journal -Biological Sciences Series, 2024)
This study was conducted with the aim of evaluating the effect of heat stress on some productivity indicators of broilers, and evaluating the effect of some food additives as treated materials . The study was conducted on 180 chick meat hybrids (ROSS), randomly distributed in three treatments, each treatment included 60 chicks, and each treatment was divided into three replicates, with 20 chicks in each replicate. The housing and care conditions were the same for all replicates from the first day of chick life until the age of 28 days, after which heat stress was applied to only two treated birds starting from the age of (28 - 42) days, and a mixture of food additives was used through drinking water (COOLIX by 1g /1L and Ultra Care compound in a ratio of 1ml/1L) to the first treated birds that were stressed and treated T1(H.S.T) while the second treatment birds exposed T2(H.S) to stress, and were left without any food additives, while the third treatment was left T3(cont) as a control under optimal care conditions. The results showed a decrease in the mortality rate in the treatment T1(H.S.T) (3,33%) compared with T2(H.S) (16.66%), while no deaths were recorded in the control treatment T3(cont). and the results showed that the average weight For the studied treatments it was almost the same before applying heat stress, in the sixth week, significant differences were observed between T3(cont) (2650g) ​​and each of (1950g) T2(H.S) and (2250g) T1(H.S.T), and the average feed consumption at T2(H.S) decreased by 12,793 % at the fifth week of bird life While in T1(H.S.T) the percentage of decrease in the average feed consumption was 6.89%, while in the sixth week, T (H.S) recorded a decrease of 10.73% and T1 (H.S.T) a decrease of 6.28%, and the best conversion factor was recorded in The fifth week at (1.64) T3(cont) followed by T1(H.S.T) (1.71), then T2(H.S)(1.75), and these results were similar in the sixth week, but they were clearer, and T2(H.S) recorded the worst conversion factor ( 2.05), while T3(cont) achieved the best conversion factor (1.69), also the average productivity index of its birds recorded the highest value at the ages of 35 and 42 (331,01), (374,92) respectively, and T1(H.S.T) also excelled as it reached Productive evidence also during the ages of birds 35 and 42 (297.33), (301.59) on treatment T2(H.S), which recorded the lowest values ​​in the mean productivity index (223.70) at the age of 35 days, and (188.75) at the age of 42 days. Key words: poultry, heat stress, productive health.